Distinct miRNA profiles in human amniotic tissue and its vesicular and non-vesicular secretome - Chaves-Solano, Nefertiti; Kau-Strebinger, Silvio; Oesterreicher, Johannes; Pultar, Marianne; Holnthoner, Wolfgang; Grillari, Johannes; Hennerbichler, Simone; Brandstetter, Andreas; Spittler, Andreas; Hackl, Matthias; Wolbank, Susanne; Banerjee, Asmita; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe human amniotic membrane (hAM) has largely been used in tissue regeneration and wound healing applications. A promising alternative to decellularized hAM or isolated cells is the usage of native viable hAM which contains and releases cell-derived bioactive factors that are known to enhance tissue regeneration. MicroRNAs (miRNAs) are known regulators of gene expression at post-transcriptional level and are important drivers of regeneration processes in several tissues. In this study, we characterized the miRNA profile of hAM tissue and its vesicular and non-vesicular secretome in the reflected and placental hAM as two spatially and physiologically distinct regions.MethodsExtracellular vesicles were enriched from the secretome by size exclusion chromatography (SEC). Small RNAs were determined by Next Generation Sequencing in the conditioned medium and in tissue.ResultsAfter SEC, we identified predominantly small hAM-derived EVs (≤200 nm) expressing CD81. The highest percentage of miRNA relative to all mapped reads was found in tissue (15%–40%), while 2%–15% were protein-bound and 3%–6% associated with EVs. Unsupervised clustering revealed distinct clusters of miRNA expression according to sample fraction (EV-associated, protein-bound, and tissue) and amniotic regions (reflected, placental). Gene ontology analysis linked EV-associated and tissue miRNAs to (smooth) muscle proliferation, while protein-bound miRNAs were associated with connective tissue development, chondrocyte differentiation and glial cell proliferation. Furthermore, correlation analysis of tissue miRNAs and extracellular expression identified EV-associated and protein-bound miRNAs specifically released from the tissue.ConclusionThese findings support the assumption that native viable hAM could serve as a miRNA source for applications in regenerative medicine.